The economic incentives of international conflicts a theoretical exposition - Andal, Emmanuel Genesis T. (2016)
This paper explores the event in which a country imposes its power on another country to improve its welfare. It constructs a model of the economic incentives of international armed conflicts and investigates the role of power relations in the furtherance of national welfare. The central result is that in case of an armed conflict, the country with the higher probability of winning has greater wealth and will aim for a larger value of the stake from the armed conflict. Furthermore, as the probability of winning the war rises, the price of the stake the country is willing to pay increases.
Keywords: War -- Economic aspects; International economic relations